The occurrence of passive intermodulation and troubleshooting in Thailand mobile industry - Chaisang, Aditep; Anantapreecha, Sinchai; Promwong, Sathaporn (My University, 2020)
This topic report about Passive Intermodulation(PIM) that can occurred in mobile indoor networks. We findout and troubleshoot this phenomenon by PIm tester. We reduced or adjusted PIM to acceptable level of IEC 62037 standard. This paper first describe the basic principle that PIM can generated and the mathematics backgrounds. PIM is occurred from nonlinear characteristics of all junctions in the networks. When we send two or more modulated signals in the same nonlinear network, PIM occurred and reduced signal quality.
Keywords: Network Nonlinearity; Passive Intermodulation(PIM); PIM Troubleshooting